Effect of Processing Conditions on Calcium Content, Firmness, and Color of Papaya in Syrup - Lovera, Nancy Noelia (2014)
Calcium impregnation is used as a pretreatment in the processing of papaya in syrup. The effect of process temperature (30 and 45°C), calcium source (calcium gluconate and calcium lactate), calcium concentration (0.5 and 1.5% w/w), and pH (4.2 and 6) were studied. The mineral source affected significantly the calcium uptake and the fruit firmness, and therefore, the product quality maximum content of calcium in the fruit was 240 and 72 mg/100 g fresh fruit in 8 h of treatment with calcium lactate and calcium gluconate, respectively. Greater firmness was observed in samples impregnated with calcium lactate. Impregnation treatments did not affect the surface color of fruit. Finally, the effect of cooking in sucrose syrup on product quality attributes (calcium retention, firmness, and color) was analyzed. Cooking in syrup had a positive effect on tissue firmness, despite the decrease of calcium content. During cooking in syrup, calcium content of treated fruit decreased between 9% and 37%. However, the calcium content of fruit in syrup was up to 6 times higher than in fresh fruit. Moreover, the cooking stage had a strong influence on color parameters, leading to a processed product darker than fresh fruit.